Village Financial Management in Lumban Pea Village, Toba Regency - Elisabeth, Duma Megaria; Saragih, Rintan; Nadapdap, Kristanty M.N.; Napitupulu, Junika; Purba, Dimita H.P.; Rumapea, Melanthon; Simanjuntak, Wesly A.; Silitonga, Ivo Maelina; Simanjuntak, Gracesiela Y.; Marbun, Sondang; Sipayung, Saur Melianna; Pratama, Putra; Tambunan, Jesica; Siregar, Elizabeth; Mesakh, Januardi (Indonesian Journal of Advanced Social Works, 2023)
This Community Service Activity aims to describe the extent of the changes in Permendagri Number 20 of 2018, Concerning Village Financial Management Guidelines, and is a revision of Permendagri 113 of 2014. Concerning Village Management Guidelines, and its relationship to Law Number 6 of 2014. 2014, About Villages. The source of data obtained is secondary data, by obtaining data from various literature on Village Laws, Government Regulations and Minister of Home Affairs regulations related to Village Financial and Wealth Management. The results of the description written are that Law 6 of 2014 concerning Villages is a reference for the creation and stipulation of Permendagri 113 of 2014 and revised to become Permendagri 20 of 2018 concerning Village Management Guidelines. The conclusion is that there are no very significant changes regarding the substance, Permendagri 113 of 2014, explaining the articles of the Village Law, and improvements are confirmed by Permendagri 20 of 2018, Concerning Village Financial Management Guidelines, which are strictly in accordance with the main duties and functions from the official who is responsible for managing village finances and assets.